1959
DOI: 10.1039/jr9590003159
|View full text |Cite
|
Sign up to set email alerts
|

641. Tautomerism and geometrical isomerism of arylazo-phenols and -naphthols. Part I. 4-phenylazo-1-naphthol

Abstract: By ERNST FISCHER and (MRs.) YAEL F. FREI.4-Phenylazo-l-naphthol (I) exists in solution as an equilibrium mixture with its tautomer, a-naphthaquinone phenylhydrazone (11). On cooling, this equilibrium shifts towards the latter (in methylcyclohexane) or towards the former (in alcohol). The alcoholic solution a t -140" contains practically only the former (I), which on irradiation with light a t various wavelengths is photoequilibrated with its cis-isomer, in analogy with other azo-compounds.Between -135" and -90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Complexation with cationic molybdenocene resulted in a large change in the absorption spectrum. The band at 420 nm decreased considerably and shifted to 470 nm; this shift can be attributed to the formation of the hydrazone form [15]. The present result is compatible with the study of Kishimoto and coworkers [17], who reported that, in tautomerism of 4-(4 0 -substituted-phenylazo)-1-naphthol [azo form vs. hydrazone form], the hydrazone form predominates with electronwithdrawing substituents.…”
Section: Synthesis Of a Photosensitive Calix[4]arene-based Molybdenocenesupporting
confidence: 95%
See 1 more Smart Citation
“…Complexation with cationic molybdenocene resulted in a large change in the absorption spectrum. The band at 420 nm decreased considerably and shifted to 470 nm; this shift can be attributed to the formation of the hydrazone form [15]. The present result is compatible with the study of Kishimoto and coworkers [17], who reported that, in tautomerism of 4-(4 0 -substituted-phenylazo)-1-naphthol [azo form vs. hydrazone form], the hydrazone form predominates with electronwithdrawing substituents.…”
Section: Synthesis Of a Photosensitive Calix[4]arene-based Molybdenocenesupporting
confidence: 95%
“…The spectrum of 6 is characterized by the presence of one absorption maximum at around 420 nm; this value is closely similar to published data on 4-arylazo-1-naphthols [15] and p-nitrophenylazo-substituted calix [4]arenes [16], suggesting that 6 exists as the azo form. Complexation with cationic molybdenocene resulted in a large change in the absorption spectrum.…”
Section: Synthesis Of a Photosensitive Calix[4]arene-based Molybdenocenesupporting
confidence: 74%
“…Structural changes should be similarly expected to provide a road to finely tune the kinetics for thermal return from the photoactivated cis stereoisomer, which is known to be faster than the corresponding azobenzene series. [29][30][31] Azobenzenes are additionally well known for the robustness of their photochromism: [32,33] 2-hydroxyazobenzenes should exhibit no significant fatigue upon multiple photocycles that lead to proton pulses. Eventually, their ionization that accompanies proton photorelease during the trans-to-cis photoisomerization could further enlarge the broad field of relevance of the azobenzene moiety, which has been extensively used to photocontrol the behavior of small molecules as well as of natural and synthetic macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of their tautomeric ratios on the solvent and substituent effects has been intensively studied quantitatively in the last ten years. 8-12 However, there are only few studies describing temperature effect, especially the changes observed at low temperatures, [13][14][15] and then only qualitatively.…”
Section: Introductionmentioning
confidence: 99%